Correction: In vitro vascularization of tissue engineered constructs by non-viral delivery of pro-angiogenic genes. (29th January 2021) - Moreira, Helena R.; Raftery, Rosanne M.; da Silva, Lucília P.; Cerqueira, Mariana T.; Reis, Rui L.; Marques, Alexandra P.; O'Brien, Fergal J.
Abstract : Correction for ' In vitro vascularization of tissue engineered constructs by non-viral delivery of pro-angiogenic genes' by Helena R. Moreira et al., Biomater. Sci., 2021, DOI: ; 10.1039/d0bm01560a .